2016
DOI: 10.1097/tp.0000000000000927
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Efficacy and Biocompatibility of Encapsulated Islet Transplantation With Chitosan-Coated Alginate Capsules in Mice and Canine Models of Diabetes

Abstract: The efficacy and biocompatibility of chitosan-alginate capsules were demonstrated in xenogeneic and allogeneic islet transplantations using small and large animal models of diabetes. This capsule might be a potential candidate applicable in the treatment of type 1 diabetes mellitus patients, and further studies in nonhuman primates are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…First, fibrosis forms around the capsule after transplantation, which not only blocks the movement of oxygen and nutrients but also triggers a foreign body reaction (De Groot, Schuurs, & van Schilfgaarde, ; Fritschy et al, ). To minimize the fibrotic reaction around alginate capsules, our group used chitosan for the second layer coating on the alginate microcapsules and demonstrated a remarkable decrease in fibrotic reactions (Yang et al, ). Second, hypoxia develops because there is no blood vessel formation in the early stage of transplantation, and oxygen supply to the transplanted encapsulated islets in the peritoneal cavity of the recipient is supplied only by diffusion (Krishnan & Ko, ).…”
Section: Introductionmentioning
confidence: 99%
“…First, fibrosis forms around the capsule after transplantation, which not only blocks the movement of oxygen and nutrients but also triggers a foreign body reaction (De Groot, Schuurs, & van Schilfgaarde, ; Fritschy et al, ). To minimize the fibrotic reaction around alginate capsules, our group used chitosan for the second layer coating on the alginate microcapsules and demonstrated a remarkable decrease in fibrotic reactions (Yang et al, ). Second, hypoxia develops because there is no blood vessel formation in the early stage of transplantation, and oxygen supply to the transplanted encapsulated islets in the peritoneal cavity of the recipient is supplied only by diffusion (Krishnan & Ko, ).…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study has shown that coating alginate microcapsules with chitosan significantly improved its biocompatibility by reducing PFO. In this study, the authors showed that chitosan-coated alginate microcapsules significantly reduced PFO and normalized blood glucose levels for up to 1 year both in a canine allotransplantation and rodent xenotransplantation model [125]. However, despite all the surface-modification strategies to reduce PFO and improve graft survival in small animal models, as outlined above, none of them have been successful in large animals, thereby undermining the clinical significance of the above approaches.…”
Section: Modification Of Alginate Microcapsulesmentioning
confidence: 84%
“…Tuch et al [20] reported thick fibrous tissue around intraperitoneally transplanted micro-encapsulated human islets 16 months after transplantation [20]. On the other hand, Yang et al [46] reported that chitosan-coating improved the biocompatibility of alginateencapsulated islets, enabling long-term function of intraperitoneally transplanted microencapsulated allogeneic islets [46]. Since EVOH has excellent biocompatibility, our EVOH bag causes minimal foreign body reactions and EVOH-enveloped macro-encapsulated islets are expected to exert their function for a long period of time.…”
Section: Discussionmentioning
confidence: 99%